Dunia Islam Abad 19 sampai 21: Penetrasi dan Pembebasan dari Kolonialisme Barat dan Kebangkitan Dunia Islam - Raudatul Jannah; Ansar Tohe (Al-Kindi, 2026)
The period spanning the 19th to the 21st centuries represents the most crucial phase in the modern history of the Islamic world, characterized by the dialectic between the collapse of traditional hegemony, the penetration of Western colonialism, and movements for liberation and renaissance. This study aims to map the geopolitical, intellectual, and socio-religious transformations within Muslim-majority regions over the last three centuries. In the 19th century, the decline of major empires—such as the Ottoman, Safavid, and Mughal—opened the way for the expansion of Western imperialism across military, economic, and cultural spheres. This penetration triggered an identity crisis while simultaneously spurring the emergence of early 20th-century liberation movements that successfully gave rise to new nation-states in the Middle East, South Asia, and Southeast Asia. Following decolonization, the Islamic world entered a 21st-century era of resurgence, marked by the repoliticization of Islam, institutional modernization, and active participation in the global economy through the Sharia finance sector and international diplomacy. The study employs a historical research method and a multidimensional approach (socio-historical and political-economic) to analyze Western penetration, liberation movements, and the resurgence of the Islamic world from the 19th to the 21st centuries. Data sources include primary data—such as colonial treaty documents (e.g., the Sykes-Picot Agreement), manuscripts and the thought of renaissance figures (Jamaluddin al-Afghani, Muhammad Abduh, Rashid Rida), and independence movement manifestos from Asia and Africa—and secondary data, comprising modern Islamic history textbooks, reputable scholarly journals on Middle Eastern and Islamic studies, and relevant dissertations and prior research reports. In conclusion, the transition from an era of colonial subjugation to modern independence demonstrates that Islam is not merely a religious identity but a civilizational force capable of adapting and responding dynamically to modernity.